ARMENIA: A DEFENSE REFORM THROUGH THE LOOKING GLASS - TELATIN, Michela (CENTRAL ASIA AND THE CAUCASUS, 2009)
Armenia can be considered as the Switzerland of the Caucasus, both having a mountainous, lacustrine, and landlocked territory. Armenia’s current borders have been unable to contain the marvels of its ancient civilization; of its scattered nationality; and its historical heritage. The solidity of its culture has clashed during centuries with an unstable surrounding environment, as the Caucasus has been an area of confluence and contrasts.1 Historically Armenia has been a country located between empires, the Ro-mans and the Parthians; the Arab and the Byzantine and found itself “as a vessel of fragile earthenware, obliged to journey in company with many vessels of iron.”2 Thus, Armenia has been a country between empires, but also a country linking empires; a nation between clashing cultures, but also a nation linking cultures, and people. Armenia, then, has been a launching pad for a new be-ginning; it will be the aim of this paper to find out if Armenia also marks a new interpretation of cur-rent policies linking development and security concerns. The background of what makes Armenia the focus of this paper is the management of its national security strategy permeated by its foreign policy of complementarity.3 This 360-degree foreign policy bears the influence and the balance of power between the different players in the Caucasian region. This might be the reason why, in recent years, Armenia has chosen a path of defensereforms supported by NATO but which contains the technical language of Security Sector Reform (SSR) policies.4 In this case, this conceptual com-plementarity does not aim at bridging a Cold War divide, but a policy divide whose reasons need investigation. The objective of this paper is to clarify why the Armenia’s defense reform has included the language of SSR policies without actually implementing these policies. I contend that being able to “talking SSR” has become synonymous of talking the language of democracy. Armenia needs this conceptual complementarity for reassuring the West about the capacity of its democratic structures to manage the defense sector, while serving its national interests of having an army capable of facing military threats. Ultimately, this is indeed the strength of the SSR-language when it is used outside a SSR-framework: it becomes an onomatopoeic policy sound of reassurance for Western-type democratic states.